Cadmium Adsorption on Chitosan/Chlorella Biomass Sorbent Prepared by Ionic-Imprinting Technique - Anis Shofiyani; Narsito Narsito; Sri Juari Santosa; Sri Noegrohati; Titin Anita Zahara; Endah Sayekti (Universitas Gadjah Mada, 2015)
Ionic-Imprinted Chitosan/Chlorella biomass sorbent (IICCb) has been synthesized for selective adsorption of Cd(II) adsorption. IICCb was prepared by coating Cd(II)-complexed-chitosan hydrogel on the biomass surface followed by cross-linking procedure. Cd(II)-imprinting ions were then eluted using Na2EDTA solution to provide a specific template for binding sites of Cd(II). Batch adsorption was carried out as function of initial pH, contact time, and initial concentration of the Cd(II) solution. Result showed that the optimum adsorption of Cd(II) was found at pH 4-6. Study of pseudo-second order kinetic showed that the adsorption of Cd(II) on IICCb went faster than that on Ionic-Imprinted Chitosan (IIC) or Non-Imprinted Ionic Chitosan/Chlorella sorbent (NIICCb). The maximum Cd(II) adsorption capacity as obtained from Langmuir adsorption isotherm was found to be 53.76 mg/g on IICCb, that was comparatively higher than that on IIC (44.44 mg/g) or on NIICCb (51.02 mg/g) adsorbent.